Antiviral activity of Cymbopogon nardus SWB6 and SWB9 extract fractions against Newcastle disease virus - Nur Eliyana, Mohd Redhuan (Universiti Malaysia Sarawak, UNIMAS, 2008)
Newcastle disease is a contagious viral infection among poultry. Poultry contribute a lot in livestock and economic sector. Therefore, many measures were taken in order to control this disease. This study was conducted to study the antiviral activity of SWB6 and SWB9 fractions of Cymbopogon nardus extract against Newcastle Disease Virus (NDV) on different level of fractions and virus concentration. Prior to addition of extract fractions, NDV was inoculated on the Vero cells and incubated for 10 minutes. The antiviral activity was determined by cell viability assay using ELISA reader. The significant difference among all treatment was analyzed by performing factorial design using SPSS. The result revealed that SWB6 showed higher cell viability than SWB9. In addition, both fraction and virus concentrations showed significant different in cell viability. However, there is no detectable association of interaction between the three factors.